Performance Pay and Offshoring. Issue 2 (14th December 2015) - Dinopoulos, Elias; Tsoulouhas, Theofanis
Abstract : In this paper, we construct a North–South general equilibrium model of offshoring, highlighting the nexus among endogenous effort‐based labor productivity and the structure of wages. Offshoring is modeled as international transfer of management practices and production techniques that allow Northern firms to design and implement performance compensation contracts. Performance–pay contracts address moral hazard issues stemming from production uncertainty and unobserved worker effort. We find that worker effort augments productivity and compensation of those workers assigned to more offshorable tasks. An increase in worker effort in the South, caused by a decline in offshoring costs, an increase in worker skill, or a decline in production uncertainty in the South, increases the range of offshored tasks and makes workers in the North and South better off. An increase in Southern labor force increases the range of offshored tasks, benefits workers in the North, and hurts workers in the South. International labor migration from low‐wage South to high‐wage North shrinks the range of offshored tasks, makes Northern workers worse off and Southern workers (emigrants and those left behind) better off. Higher worker effort in the North, caused by higher worker skills or lower degree of production uncertainty, decreases the range of offshored tasks and benefits workers in the North and South.